Implementation Of Wage Unit Results In Meeting The Decent Living Needs (KHL) Of Batik Workers - Yeski Putri Utami; Mudiana Permata Sari; Jarot Marsono (Eduvest - Journal of Universal Studies, 2024)
Wage based on unit of output is a wage paid based on the production or quantity of goods produced by the worker, in this research, the amount of batik produced by the batik maker. This study aims to determine the implementation of piece-rate wages for batik workers, Pekalongan (Batang) area in Central Java and Cirebon, West Java to see the welfare of batik workers. This research uses qualitative methods with data collection instruments in the form of interviews and field observations. The magnitude of the poverty line and the average monthly per capita expenditure of the community at the provincial and city levels are indicators in determining the welfare level of workers. The results show that the piece-rate wages received by batik workers are higher than the city and provincial poverty lines, but still low when compared to the average monthly per capita expenditure at the provincial and city levels. Nevertheless, employers can determine the amount of wages below the government's decision if employers and workers have agreed. In conclusion, the wages received by the batik workers have not been able to fulfill the KHL of the batik workers optimally. However, batik makers are considered prosperous because they have fulfilled Article 36 Paragraph (2) of Government Regulation No. 36 of 2021 where wages in Small and Medium Enterprises, especially batik, have fulfilled at least 50% of the average consumption of the provincial community and at least 25% above the poverty line at the provincial level.